If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(X) = (2x + -1)(x + 3)(x + -2) Multiply F * X FX = (2x + -1)(x + 3)(x + -2) Reorder the terms: FX = (-1 + 2x)(x + 3)(x + -2) Reorder the terms: FX = (-1 + 2x)(3 + x)(x + -2) Reorder the terms: FX = (-1 + 2x)(3 + x)(-2 + x) Multiply (-1 + 2x) * (3 + x) FX = (-1(3 + x) + 2x * (3 + x))(-2 + x) FX = ((3 * -1 + x * -1) + 2x * (3 + x))(-2 + x) FX = ((-3 + -1x) + 2x * (3 + x))(-2 + x) FX = (-3 + -1x + (3 * 2x + x * 2x))(-2 + x) FX = (-3 + -1x + (6x + 2x2))(-2 + x) Combine like terms: -1x + 6x = 5x FX = (-3 + 5x + 2x2)(-2 + x) Multiply (-3 + 5x + 2x2) * (-2 + x) FX = (-3(-2 + x) + 5x * (-2 + x) + 2x2 * (-2 + x)) FX = ((-2 * -3 + x * -3) + 5x * (-2 + x) + 2x2 * (-2 + x)) FX = ((6 + -3x) + 5x * (-2 + x) + 2x2 * (-2 + x)) FX = (6 + -3x + (-2 * 5x + x * 5x) + 2x2 * (-2 + x)) FX = (6 + -3x + (-10x + 5x2) + 2x2 * (-2 + x)) FX = (6 + -3x + -10x + 5x2 + (-2 * 2x2 + x * 2x2)) FX = (6 + -3x + -10x + 5x2 + (-4x2 + 2x3)) Combine like terms: -3x + -10x = -13x FX = (6 + -13x + 5x2 + -4x2 + 2x3) Combine like terms: 5x2 + -4x2 = 1x2 FX = (6 + -13x + 1x2 + 2x3) Solving FX = 6 + -13x + 1x2 + 2x3 Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Divide each side by 'X'. F = 6X-1 + -13xX-1 + x2X-1 + 2x3X-1 Simplifying F = 6X-1 + -13xX-1 + x2X-1 + 2x3X-1
| p=50-8x+3x^2 | | 4=52/f | | 15=-7/8(45-X) | | 3z=1.3+2.9 | | f+27=42 | | 3d+5=5-10 | | 4=6+a | | -6n+21= | | r-25=49 | | 5y+12=42 | | 0.09xX=51.29 | | m-37=49 | | 44=h-33 | | 8/x=12/3 | | 8w-15w=35 | | 55=k-29 | | Y/3.5=10 | | 41=y+19 | | y-7=2.66(x-10) | | 4[4-(3-7x)]+2x=5(6x+3)-11 | | -1+2=2+3(2-1) | | 39+b=50 | | 3/8=x/1 | | c-3=13 | | 3(sin)x+1=(sin)x | | 10/1=x/2 | | 12x+9=8x+3+4x | | x+24=28 | | 62+5x=3(-x+3)-11 | | .09x+.11(x+9000)=2590 | | 2f=86 | | 33=-3f |